Introduction: feature issue on optical molecular probes, imaging, and drug delivery - Campagnola, Paul (Optical Society of America, 2014)
The editors introduce the Biomedical Optics Express feature issue “Optical Molecular Probes, Imaging, and Drug Delivery,” which is associated with a Topical Meeting of the same name held at the 2013 Optical Society of America (OSA) Optics in the Life Sciences Congress in Waikoloa Beach, Hawaii, April 14-18, 2013. The international meeting focused on the convergence of optical physics, photonics technology, nanoscience, and photochemistry with drug discovery and clinical medicine. Papers in this feature issue are representative of meeting topics, including advances in microscopy, nanotechnology, and optics in cancer research.